Antimicrobial Activity of Quercus infectoria Gall and Its Active Constituent, Gallic Acid, against Vaginal Pathogens - Mozhgan Mehri Ardestani; Atousa Aliahmadi; Tayebeh Toliat; Abdolhossein Dalimi; Zohreh Momeni; Roja Rahimi (Tehran University of Medical Sciences, 2019)
Vaginal infections are one of the most common reasons a woman visits a gynecologist. The increased resistance to conventional antibiotics is one of the main reasons for searching and developing new antimicrobial agents, especially those of natural origin. In traditional Persian medicine, the gall of Quercus infectoria has been claimed to eliminate vagina and cervix from excessive discharge. So, the aim of the present study was to evaluate the antimicrobial activity of ethanolic extract of Quercus infectoria gall as well as its active constituent, gallic acid, against some vaginal pathogens. In this study, the ethanolic extract of Quercus infectoria gall was obtained by maceration and standardized based on amount of gallic acid. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of this extract as well as its active compound, gallic acid, were determined against Candida spp., Gardnerella vaginalis, Escherichia coli, Staphylococcus aureus, Streptococcus agalactiae, Trichomonas vaginalis and Lactobacillus acidophilus. The results demonstrated remarkable activity of ethanolic extract of Quercus infectoria gall against investigated pathogens with MIC and MBC in the range between 0.125 mg/ml and 16 mg/ml. The most inhibitory and bactericidal activity was observed on Streptococcus agalactiae and Staphylococcus aureus. The effects of gall dried ethanolic extract on Trichomonas vaginalis showed 100 % inhibition of the parasitic growth with concentration of 800 µg/ml after 24 h incubation. The antimicrobial and anti-trichomonas activity of extract was more than gallic acid. It seems that ethanolic extract of Quercus infectoria gall could inhibit the growth of vaginal pathogens. Further preclinical and clinical studies are required to confirm the efficacy of this natural extract in vaginitis.